Studies On The Comparative Effect Of Rosemary Extract And Butylated Hydroxy Anisole On The Keeping Quality Of Value Added Chicken Meat Sausages Chicken Meat Sausages - Reddy, D.Maheswara; Babu, A.Jagadeesh; Rao, B.Eswara; Moorthy, P.R.S.; Gupta, R.S.D. (Journal of Meat Science, 2014)
The present investigation has been designed to know the effect of rosemary extract on the keeping quality of value added chicken meat sausages and to compare the effect of rosemary with synthetic antioxidant i.e. BHA. Significantly (P
Keywords: Comparative Effect; Rosemary Extract; Butylated Hydroxy Anisole; Chicken Meat Sausages